(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Economically, developing region like Dhule district mainly depends on climate sensitive activities such as agriculture for their livelihood and are particularly vulnerable to rainfall variability. Rainfall variability affects the production of traditional crops like Jowar, Bajara, Maize, Cotton, Oilseeds, Pulses crops, increases crop diseases incidence and causes drastic reductions in soil fertility. It has been reported; in many parts of the country that rainfall variability has been attributed to changes in production or will be responsible for future change in agricultural production dynamics. It is also observed that, in general, short rainy seasons and much more variable rainfall periods between June and September. The threat of food insecurity has increased as a result of the phenomenon of rainfall variability among many farm communities. Seasonal rainfall variability has a profound effect on soil moisture, availability especially for the crop production. Overall, the soil moisture reduces with high rainfall variability in the agricultural region like Dhule district where rainfed agriculture is predominant. In recent years, it is seen that in Dhule district, minor rainy seasons have become much drier and shorter which are unfavourable for agricultural development in the region. The crop production in the study region is predominantly rainfed, exposing this major livelihood activity to the variability or change in rainfall pattern. Generally, the effect of the amount of rainfall and variability on crop production varies with types of crops cultivates, types and properties of soils and climatic conditions of a given area.The fluctuations in amount of annual rainfall and their impact on yield of major crops have been studied in the present work